2017
DOI: 10.1016/j.joen.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Peptide LL-37 as a Possible Adjunct for the Proliferation and Differentiation of Dental Pulp Stem Cells

Abstract: These results demonstrated that LL-37 was biocompatible at these concentrations and increased the number of viable cells, especially during the initial period. The 10 μg/mL concentration arrested the cell cycle and increased expression of the DSPP protein and gene, which indicates that this peptide contributes to odontoblastic differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…bone-related collagen type I gene (COL 1, Figure 5C) confirmed that the cell differentiation moved toward the chondrogenic phenotype and not toward the osteogenic one. Such findings were predictable: as previously discussed in section AMPs Cytocompatibility, LL-37 was shown to be effective in promoting stem cells differentiation and adverse effects were not observed at the same concentrations (5-20 µg/ml) (Yang et al, 2016;Milhan et al, 2017;Yu et al, 2018). Conversely, at the best of our knowledge, Nisin was not assayed for effects on the stem cell commitment; however, the lack of toxic effects noticed in the cytocompatibility assay allowed for the speculation that Nisin could be also regarded as inert, not inducing any impairments to the stem cell commitment.…”
Section: Chondrogenesis In Cell Monolayerssupporting
confidence: 67%
See 1 more Smart Citation
“…bone-related collagen type I gene (COL 1, Figure 5C) confirmed that the cell differentiation moved toward the chondrogenic phenotype and not toward the osteogenic one. Such findings were predictable: as previously discussed in section AMPs Cytocompatibility, LL-37 was shown to be effective in promoting stem cells differentiation and adverse effects were not observed at the same concentrations (5-20 µg/ml) (Yang et al, 2016;Milhan et al, 2017;Yu et al, 2018). Conversely, at the best of our knowledge, Nisin was not assayed for effects on the stem cell commitment; however, the lack of toxic effects noticed in the cytocompatibility assay allowed for the speculation that Nisin could be also regarded as inert, not inducing any impairments to the stem cell commitment.…”
Section: Chondrogenesis In Cell Monolayerssupporting
confidence: 67%
“…In fact, cytotoxicity of LL-37 at the concentrations of 25 and 50 µg/ml was significant in comparison with the untreated control causing death of >70% cells (Figure 1B, p < 0.05 indicated by * ). Unlike for Nisin, some literature reports can be found regarding direct effects of LL-37 toward stem cells showing that the peptide was effective in promoting stem cell proliferation and differentiation: dental pulp stem cells (at 5-10 µg/ml LL-37 concentration, Milhan et al, 2017), adipose derived stem cells (at 2.5-20 µg/ml LL-37 concentration, Yang et al, 2016), and bone marrow derived stem cells (at 10 µg/ml LL-37 concentration, Yu et al, 2018). Still, in these works the applied LL-37 concentrations ranged between 5-20 µg/ml, thus confirming the possible use of this peptide only at low concentrations.…”
Section: Amps Cytocompatibilitymentioning
confidence: 99%
“…Indeed, the multifunctionality of antimicrobial peptides in the clearance of infection and in modulating inflammation points to their therapeutic usefulness in endodontic therapies 33 . Although data are limited on the regenerative effects of antimicrobial peptides, LL-37 has been shown to be biocompatible with dental pulp stem cells in vitro and has been suggested as a possible adjunct for their enhanced proliferation and differentiation 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Since KR-12 and several other antibacterial peptides have the ability to promote stem cell differentiation (Krasnodembskaya et al, 2010; Alcayaga-Miranda et al, 2017; Milhan et al, 2017; Li et al, 2018), KR-12-a5 may also have the potential to promote HBMSC osteogenic differentiation. Associated with the excellent anti-inflammatory properties of this small peptide, KR-12-a5-mediated regulation of osteogenesis can be expected under inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%